A review of carbon dots and their composite materials for electrochemical energy technologies. Issue 5 (22nd July 2021) - Liu, Yiming; Roy, Swagata; Sarkar, Samrat; Xu, Jiaqiang; Zhao, Yufeng; Zhang, Jiujun
Abstract: Carbon dots (CDs) and their composites as energy storage materials and electrocatalysts have emerged as new types of quasi‐zero‐dimensional carbon materials. CDs can provide a large specific surface area, numerous electron–electron hole pairs, adjustable heteroatom doping, rich surface functional groups, and so on. However, the roles and functional mechanisms of CDs and their composite materials in the enhancement of electrochemical performance remain unclear and need to be understood in depth. Based on the most recent literature, this paper comprehensively reviews the synthesis methods and applications of various categories of CDs and their composites as electrode materials of supercapacitors, lithium‐ion batteries, sodium‐ion batteries, and potassium‐ion batteries, and as electrocatalysts for hydrogen evolution, oxygen evolution, and oxygen reduction reactions in metal–air batteries, fuel cells, and water electrolysis. To facilitate further research and development, several important aspects related to CDs and their composite materials are summarized with analysis of the technical challenges in practical applications and discussion of the possible development perspectives. Abstract : In this study, various categories of carbon dots, their preparation methods and applications as electrode materials of supercapacitors, Li‐ion batteries, Na‐ion batteries, and K‐ion batteries, and as electrocatalysts for hydrogen evolution, oxygen evolution, and oxygen reduction reactions in metal–air batteries, fuel cells, and water electrolysis are comprehensively reviewed based on the most recent literature reports.